Targeted deletion of the zebrafish actin-bundling protein L-plastin (lcp1) - Kell, Margaret J.; Riccio, Rachel E.; Baumgartner, Emily A.; Compton, Zachary J.; Pecorin, Paul J.; Mitchell, Taylor A.; Topczewski, Jacek; LeClair, Elizabeth E. (PLOS ONE, 2018)
Regulation of the cytoskeleton is essential for cell migration in health and disease. Lymphocyte cytosolic protein 1 (lcp1, also called L-plastin) is a hematopoietic-specific actin-bundling protein that is highly conserved in zebrafish, mice and humans. In addition, L-plastin expression is documented as both a genetic marker and a cellular mechanism contributing to the invasiveness of tumors and transformed cell lines. Despite L-plastin’s role in both immunity and cancer, in zebrafish there are no direct studies of its function, and no mutant, knockout or reporter lines available. Using CRISPR-Cas9 genome editing, we generated null alleles of zebrafish lcp1 and examined the phenotypes of these fish throughout the life cycle. Our editing strategy used gRNA to target the second exon of lcp1, producing F0 mosaic fish that were outcrossed to wild types to confirm germline transmission. F1 heterozygotes were then sequenced to identify three unique null alleles, here called ‘Charlie’, ‘Foxtrot’ and ‘Lima’. In silico, each allele truncates the endogenous protein to less than 5% normal size and removes both essential actin-binding domains (ABD1 and ABD2). Although none of the null lines express detectable LCP1 protein, homozygous mutant zebrafish (-/-) can develop and reproduce normally, a finding consistent with that of the L-plastin null mouse (LPL -/-). However, such mice do have a profound immune defect when challenged by lung bacteria. Interestingly, we observed reduced long-term survival of zebrafish lcp1 -/- homozygotes ( 30% below the expected numbers) in all three of our knockout lines, with greatest mortality corresponding to the period (4–6 weeks post-fertilization) when the innate immune system is functional, but the adaptive immune system is not yet mature. This suggests that null zebrafish may have reduced capacity to combat opportunistic infections, which are more easily transmissible in the aquatic environment. Overall, our novel mutant lines establish a sound genetic model and an enhanced platform for further studies of L-plastin gene function in hematopoiesis and cancer.